The Application of TiO2 for the Photocatalytic Conversion of the Nitrogen Oxides - NO and NO2 - Kafizas,A (2025)
Nitric oxide (NO) and nitrogen dioxide (NO2) gases are together referred to as NOx, which are highly toxic to humans when inhaled. Today, NOx gas is predominantly formed by human activities, such as combustion processes. Once dispersed, NOx emissions are challenging to remedy, as concentrations in the atmosphere are typically lower than a part per million. Nevertheless, TiO2-based photocatalysts can treat dilute levels of NOx, functioning passively using ambient light. In this chapter, we present recent developments in the use of TiO2 -based photocatalysts for remediating NOx, covering field trials of products that have been developed for various commercial applications, the rational design of more active catalysts, and future challenges and perspectives.